Analisis Dokumenter Representatif Berbasis Piloting a Constructive Feedback (PCF) sebagai Pengembangan Media Pembelajaran Pendidikan Pancasila - Muhammad Haizul Falah; Yetti Hidayatillah (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
This study aims to analyze the use of the representative documentary Jalanan produced in 2013 as a learning medium in Pancasila education subject through the Piloting a Constructive Feedback (PCF) approach for tenth-grade students at SMA Muhammadiyah 2 Paciran. A qualitative descriptive method was employed, with data collected through observation, closed and open questionnaires, and informal interviews. The results indicate that the documentary effectively facilitates students’ understanding of Pancasila values, particularly social justice, humanity, and the rights and responsibilities of citizens. The implementation of the PCF model encourages active student engagement in providing feedback, critical thinking, and reflecting on the meaning of the film both personally and socially. Student responses revealed an increase in empathy and awareness of social issues that were previously underappreciated. This study confirms that social-reality-based documentary media can serve as a contextual learning alternative relevant to the characteristics of Generation Z and Alpha, and is effective in strengthening value-based learning in Pancasila Education.